1999
DOI: 10.1095/biolreprod61.4.1005
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Upstream Elements Involved in Transcriptional Regulation of the Rat Testis-Specific Histone H1t Gene in Somatic Cells1

Abstract: The testis-specific histone H1t is synthesized exclusively in late pachytene primary spermatocytes during spermatogenesis. The mechanisms involved in transcriptional repression of the H1t gene during development before the spermatocyte stage and in later stages of germinal cell maturation and in nonexpressing somatic tissues are unknown. To assess the contribution of the upstream DNA sequence to H1t transcriptional silencing in nonexpressing cells, a set of histone H1t-promoted reporter vectors was constructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 46 publications
0
36
1
Order By: Relevance
“…To test this hypothesis, we performed chromatin immunoprecipitation (ChIP) experiments using affinitypurified ␣-CT antibody and primers against the H1t proximal and distal promoter region. The primers were selected based on previous studies showing that the proximal and distal regions are involved in the activation and repression of H1t expression, respectively (vanWert et al, 1998;Wolfe et al, 1999). The results revealed that immunoprecipitated full-length Brdt protein (from control testes) was found in association with the distal region of the histone H1t promoter (-806 to -1027 from the transcription initiation site), but not to the more proximal region of the promoter (Fig.…”
Section: Fig 6 Brdt Protein Is Involved In the Regulation Of Expresmentioning
confidence: 99%
“…To test this hypothesis, we performed chromatin immunoprecipitation (ChIP) experiments using affinitypurified ␣-CT antibody and primers against the H1t proximal and distal promoter region. The primers were selected based on previous studies showing that the proximal and distal regions are involved in the activation and repression of H1t expression, respectively (vanWert et al, 1998;Wolfe et al, 1999). The results revealed that immunoprecipitated full-length Brdt protein (from control testes) was found in association with the distal region of the histone H1t promoter (-806 to -1027 from the transcription initiation site), but not to the more proximal region of the promoter (Fig.…”
Section: Fig 6 Brdt Protein Is Involved In the Regulation Of Expresmentioning
confidence: 99%
“…Most of the H1t promoter regulatory elements are located within the proximal promoter, but some upstream elements also contribute to transcriptional regulation. For example, we identified a silencer region located between 875 and 948 bp upstream from the transcription initiation site [3]. In addition, an upstream TG-rich element has been identified as a binding site for a transcriptional activator [31].…”
Section: Discussionmentioning
confidence: 98%
“…The DNase I digestions were conducted in a total volume of 40 l as previously described [3]. Following DNase I digestion, the samples were extracted twice with phenol:chloroform (1:1) and DNA precipitated from the aqueous phase with 2.5 volumes of ethanol at Ϫ20ЊC for 1 h. The DNA was recovered by centrifugation for 20 min at 16 000 ϫ g at 4ЊC.…”
Section: In Vitro Dnase I Footprintingmentioning
confidence: 99%
See 2 more Smart Citations